Intensity-Modulated Radiotherapy with Concomitant Boost After Breast Conserving Surgery: A Phase I–II Trial - Macchia G (Dove Medical Press, 2020)
Gabriella Macchia,1 Savino Cilla,2 Milly Buwenge,3 Alice Zamagni,3 Ilario Ammendolia,3 Claudio Zamagni,4 Giovanni P Frezza,5 Vincenzo Valentini,6,7 Francesco Deodato,1,* Alessio G Morganti3,* 1Radiotherapy Unit, Gemelli Molise Hospital, Università Cattolica Del Sacro Cuore, Campobasso, Italy; 2Medical Physics Unit, Gemelli Molise Hospital, Università Cattolica Del Sacro Cuore, Campobasso, Italy; 3Radiation Oncology Center, Department of Experimental, Diagnostic and Specialty Medicine ‑ DIMES, University of Bologna, S. Orsola-Malpighi Hospital, Bologna, Italy; 4Addarii Medical Oncology Unit, S. Orsola-Malpighi Hospital, Bologna, Italy; 5Radiation Oncology Unit, Bellaria Hospital, Bologna, Italy; 6Dipartimento di Scienze Radiologiche, Radioterapiche ed Ematologiche, Fondazione Policlinico Universitario A. Gemelli IRCCS, UOC di Radioterapia, Rome, Italy; 7Istituto di Radiologia, Università Cattolica Del Sacro Cuore, Rome, Italy*These authors contributed equally to this workCorrespondence: Milly BuwengeRadiation Oncology Unit, Department of Experimental, Diagnostic and Specialty Medicine – DIMES, University of Bologna, S. Orsola-Malpighi Hospital, Via Giuseppe Massarenti 9, 40138, BolognaTel +39 0512143564Fax +39 0516364336Email mbuwenge@gmail.comPurpose: A concomitant boost (CB) in patients treated with postoperative radiotherapy after conservative surgery of invasive breast cancer (BC) has been suggested for treatment time reduction and therapy intensification. The aim of this analysis was to assess long-term tolerability of a CB in patients treated with postoperative intensity Modulated Accelerated RAdiotherapy (MARA).Patients and Methods: In this phase I–II trial, 321 patients with intermediate-high risk BC (pT1-4 with at least one of the following characteristics: pre or perimenopausal status, pN2-3, positive or close margins) were enrolled. Patients were treated with forward-planned intensity modulated radiotherapy (IMRT) and CB. A total dose of 50 Gy (2 Gy/fraction) and 60 Gy (2.4 Gy/fraction) was prescribed to the whole breast and the tumor bed, respectively. The potential impact of hypertension, diabetes, smoking habit, alcohol consumption, chemotherapy, and hormone therapy on both skin and subcutaneous late toxicity-free survival (LTFS) was evaluated. Survival curves were calculated using the Kaplan–Meier method.Results: Median follow-up was 52 months (range: 3– 115). Regional node irradiation, adjuvant chemotherapy and hormonal therapy were prescribed to 29.3%, 65.4% and 81.0% of patients, respectively. Five-year G2 and G3 skin LTFS were 95.6% and 100.0%, respectively. Five-year G2 and G3 subcutaneous LTFS were 80.0% and 98.6%, respectively. Only diabetes showed a significant correlation with worse G3 subcutaneous LTFS (p: 0.024). Five-year loco-regional control, metastasis-free survival, disease-free survival, and overall survival were 98.0%, 91.8%, 89.7% and 96.3%, respectively.Conclusion: IMRT combined with CB was associated with a low risk of > G2 late toxicities (0.0% and 1.4% for skin and subcutaneous tissue, respectively). The cumulative actuarial incidence of local recurrences was 2.0% despite the exclusion of low-risk patients. Our results suggest that CB is safe and effective in patients with intermediate-high risk BC.Trial Registration: ClinicalTrials.gov: NCT03471741.Keywords: breast cancer, adjuvant radiotherapy, concomitant boost, IMRT, toxicity